Pengaruh Penerapan Strategi Pembelajaran Kooperatif Tipe Think Pair Share (Tps) Terhadap Hasil Belajar IPS Kelas IX MTs Negeri 2 Medan - Rambe, Rohimah Marito; Sitorus, Masganti; Perkasa, Ripho Delzy (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this study is to assess the impact of student learning outcomes via the TPS cooperative learning model on exchange materials between Asian countries and other countries in class IX MTsN2 Medan ini 2022. That’s it decided in 2023. The research conducted is a Quasi-experimental, Quantitative study. This population consist exsclusively of class IX MTsN 2 Medan. The sample for this study consisted of 32 students in grade IX-4 (the experimental class was taught using the Think Pair Share collaborative learning model) and 32 students in grade IX-5 (the control class used the traditional learning model). was taught using a test instrumen in the form of multiple choice question served as the study instrument. Data analysis was performed using the t-tes. based on the analysis of the t-test result, we found t-count > t-table, namely 13,694>1,679. and significance leval α = 0,05, dk= n1+n2 – 2 = 32+32-2 = 62. This indicates that Ha was accepted and Ho was rejected, suggesting an impact on social science learning outcomes for students using the TPS learning model. Furthermore, there are significant differences in learning outcomes for students taught using the TPS collaborative learning model and traditional learning models. this is evidenced by the average pretest score of 22,27 and the posttest average score of 75,00 for the experimental class. In the control class, the pre-test mean was 20,94 and post-test 71,33.The results of this study suggest that the sink-pair Share learning model influencess the social science learning outcomes of class IX MTsN 2 Medan. There fore, the TPS learning model is used by school social studies teachers as her one of the social studies learning options. Moreover, the TPS learning model should be able to bring more insight to school students. Keywords: Learning Outcomes, Think Pair Share, Social Studies Education